The Existence of Information Technology Terminology Usage in Indonesian Among University Students - Syahriandi Syahriandi; Radhiah Radhiah; Trisfayani Trisfayani; Emilda Emilda (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to describe the existence and usage of Indonesian equivalents for information technology terms among university students. Employing a qualitative descriptive method, the research utilized purposive sampling to select participants. The sample consisted of 31 students from the 2023 cohort of the Indonesian Language Education program. Data were collected through a questionnaire listing commonly used information technology terms, for which students were asked to provide their Indonesian equivalents. The responses were analyzed using simple percentage calculations and then described qualitatively to illustrate the extent of usage of Indonesian terms among the students. The results show that (a) overall, 70% of the students were unaware of the Indonesian equivalents of the terms, and fewer than 50% could provide accurate equivalents for any of the 14 terms presented, and (b) the popularity of foreign information technology terms is one of the factors contributing to students' reluctance to learn or use their Indonesian counterparts.